Intraoperative Extracorporeal Carbon Dioxide Removal During Apneic Oxygenation with an EZ-Blocker in Tracheal Surgery. Issue 11 (1st June 2016) - Rispoli, Marco; Nespoli, Moana Rossella; Mattiacci, Dario Maria; Esposito, Marianna; Corcione, Antonio; Buono, Salvatore
Abstract : Tracheal surgery requires continued innovation to manage the anesthetic during an open airway phase. A common approach is apneic oxygenation with continuous oxygen flow, but the lack of effective ventilation causes hypercapnia, with respiratory acidosis. We used extracorporeal carbon dioxide removal for intraoperative decapneization during apneic oxygenation in a 64-year-old woman who was scheduled for tracheal surgery because of tracheal stenosis caused by long-term intubation. Our findings demonstrate that even after 40 minutes of total apnea, using an EZ-blocker for oxygenation and external decapneization, hemodynamic and gas exchange variables never demonstrated any dangerous alterations.